Delayed Stroke Secondary to Increasing Mass Effect after Endovascular Treatment of a Giant Aneurysm by Parent Vessel Occlusion - Blanc, Raphaël; Weill, Alain; Piotin, Michel; Ross, Ian B.; Moret, Jacques (American Journal of Neuroradiology, 2001)
Summary: A 47-year-old woman, who had lost vision in her left eye because of a giant left supraclinoid internal carotid artery aneurysm, was referred for endovascular treatment. Parent-vessel occlusion was performed to obtain circulatory exclusion of the aneurysm. Eight days after treatment, she became hemiparetic and dysphasic. Repeat angiography showed compression of the left middle cerebral artery by the swelling giant aneurysm. Preventive measures should be taken to avert worsening of mass effect when giant aneurysms become thrombotic.